1992
DOI: 10.1016/0014-5793(92)80956-h
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A processing in sympathetic neurons and release of chromogranin A fragments from sheep spleen

Abstract: Chromograam A (CGA) has been localized to the large dense cored vesicles (LDV) of sympathetic neurons SDS-PAGE and lmmunoblotlmg of soluble LDV proteins hem ox and dog adrenergic neuronal cell bodies, unonb and nerve terminals, revealed an increasing number of CGAimmunoreactive forms, consistent with proteolyt~e processing dunng axonal transport. Spleme nerve electrical stimulauon (10 Hz, 2 rain) revealed that, apart from CGA these CGA-proeessmg products are released from the sheep spleen. The secretion of CGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Their immunoblotting finding suggested a more extensive myocardial CGA processing compared to that of the adrenal medulla. As remarked by Miserez et al (1992), an additional source of cardiac CGA and/or CGA-derived fragments may result from the nerve termini innervating the heart. Weiergräber et al (2000) showed that CGA was also present in rat Purkinje conduction fibers, in both rat atrium and ventricle, as well as in H9c2 rat cardiomyocytes.…”
Section: The Cardio-circulatory Profile Of Full-length Cgamentioning
confidence: 88%
“…Their immunoblotting finding suggested a more extensive myocardial CGA processing compared to that of the adrenal medulla. As remarked by Miserez et al (1992), an additional source of cardiac CGA and/or CGA-derived fragments may result from the nerve termini innervating the heart. Weiergräber et al (2000) showed that CGA was also present in rat Purkinje conduction fibers, in both rat atrium and ventricle, as well as in H9c2 rat cardiomyocytes.…”
Section: The Cardio-circulatory Profile Of Full-length Cgamentioning
confidence: 88%
“…The immunohistochemical study verifying the presence of vasostatin‐1 in the cardiac autonomic ganglia immunohistochemically is still lacking. Since vasostatin‐1 is released at the autonomic nerve terminals upon stimulation, 6,7 it is very much possible that it exists in the cardiac autonomic ganglia. Our results indicate that vasostatin‐1 exerts a physiologic role in the cardiac autonomic ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on a series of new cardioregulatory peptides that are fragments of an acidic protein, chromogranin‐A. Vasostatin‐1 represents the N ‐terminal fragment of chromogranin‐A containing 76 amino acid residues and is released with autonomic nerve stimulation (splenic nerve electrical stimulation) 6,7 . This peptide has been shown to have strong concentration‐dependent negative inotropic effects on isolated and perfused heart preparations of eel, frog, and rat both under basal conditions, as well as after beta‐adrenergic stimulation 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…In the rat heart, CGA is stored in nonadrenergic myoendocrine atrial cells containing atrial natriuretic peptide [76] and in Purkinje fibers of the rat atrium and ventricle containing the calcium channel a1E subunit [151]. CgA-derived fragments may also originate from sympathetic nerve termini in the heart [152]. Four vasostatin-containing CgA peptides have recently been extracted from rat heart, CgA 4-113 , CgA 1-124 , CgA 1-135 and CgA , in addition to intact CgA and larger sized fragments containing the C terminus [77], indicating a less extensive CgA processing in the heart than in the adrenal medulla.…”
Section: Cardiovascular Processes a Range Of Inhibitory Responses To mentioning
confidence: 99%